2021
DOI: 10.1108/sajbs-04-2020-0100
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous impact of leverage on firm performance: empirical evidence from Bangladesh

Abstract: PurposeThe purpose of this study primarily is to investigate the heterogeneous effect of leverage on performance of the listed nonfinancial joint stock companies in Bangladesh.Design/methodology/approachA large panel sample of 165 listed nonfinancial firms under different industries of Bangladesh studied for the period 2007–2016 employing the dynamic panel approaches, namely, differenced generalized method of moments (GMM) and system GMM. The asymmetric relationship between leverage and performance is also exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
6
8
1
Order By: Relevance
“…The results are in contrast to the study by Das, Chowdhury, and Islam (2021) in Bangladesh which found a negative relationship between financial leverage and firm performance proxied as ROE and ROA. Also, Samo and Murad (2019) in Pakistan found a negative relationship between leverage and profitability (ROA and ROE).…”
Section: Discussion Of Findingscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results are in contrast to the study by Das, Chowdhury, and Islam (2021) in Bangladesh which found a negative relationship between financial leverage and firm performance proxied as ROE and ROA. Also, Samo and Murad (2019) in Pakistan found a negative relationship between leverage and profitability (ROA and ROE).…”
Section: Discussion Of Findingscontrasting
confidence: 99%
“…Prior studies have explored the firm's debt-equity mix and performance nexus from several perspectives in different countries (Akeem, Terer, Kiyanjui, &Kayode, 2014;David &Olorunfemi, 2010;Nima, Mohammad, Saeed, &Zeinab, 2012;Salim&Yadav, 2012;Uremadu&Onuegbu, 2019;Vătavu, 2015). Empirically, Das, Chowdhury, and Islam (2021) in Bangladesh, Chakraborty (2010) in India, and the study by Huang and Song (2006) in China found a negative relationship between leverage and firm performance, proxied using ROA, ROE, and EBIT. Others, such as Khan (2012) in Pakistan; Sadeghian, Latifi, Soroush, and Aghabagher (2012) in Iran also find a negative relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Financial leverage is a financial policy related to a company’s decision to finance and shows the investment of its domestic resources compared with financing through loans (Irwansyah et al , 2017). Leverage indicators have a negative impact on a firm’s value and performance in terms of return on equity and return on asset and a greater negative impact of leverage on performance in high-profitable firms than in low-profitable firms (Das et al , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…As a control variable, financial leverage (LEV), which is calculated as the ratio of total debt to total assets, has been utilized. Using dynamic panel techniques, Das et al (2021) looked at the heterogeneous impact of leverage on the performance of 165 listed nonfinancial companies in Bangladesh from 2007 to 2016 and discovered that the firms" performance was negatively impacted by leverage. However, Vo and Ellis (2017) found that there is a positive relationship between leverage and performance when the firm is using optimal leverage, and when the firm is unable to modify its capital structures, the relationship turns negative.…”
Section: Variable Descriptionmentioning
confidence: 99%